Koverte handelingsdimensies: 'n Kritiese fokuspunt in die opleiding van aspirant-opleiers - Hugo G. Van Rooyen (South African Journal of Business Management, 1992)
Covert performance dimensions: A critical focal point in the training of trainers The teaching competence of a trainer is to a large extent determined by his covert faculties. Teaching theories and models, as well as training programmes for trainers. which do not place sufficient focus on the covert performance domain are guilty of a too narrow interpretation of the essence of the teaching act. The complex nature of the covert performance domain and the important influence that the different facets thereof exert on the trainer's teaching competence are dealt with in depth. The main implications for training of trainers are indicated.
Keywords: 650